Alleviation of Retching and Feeding Intolerance After Fundoplication. (June 2014) - Cook, Robin C.; Blinman, Thane A.
Background: Although surgical intervention for gastroesophageal reflux disease (GERD) in children offers the strongest control of GERD, these results are tempered by postoperative problems such as retching, bloat, dysphagia, dumping syndrome, and postprandial hypoglycemia. We created a specialty clinic and an algorithmic approach to ameliorating these problems. Here, we present our experience with the first 60 patients. Methods : Patients referred to the clinic for feeding problems after fundoplication were tracked as part of quality improvement monitoring. Patients were treated according to a heuristic algorithm intended to reduce iatrogenic causes of feeding intolerance and to identify medical and mechanical contributors to retching. These etiological factors were tracked, along with patient responses. Results : Of the 60 initial patients, 92% completed ≥4 visits. A heuristic algorithm produced near-complete or complete resolution in 97.5% of those patients. In most patients, multiple causes contributed to retching and were commonly iatrogenic (eg, very large boluses, overfeeding, polypharmacy). Surgical failure was a relatively uncommon contributor to intolerance. Conclusions : Successful results after antireflux surgery depend both on surgical technique and on strategic postoperative feeding. The finding that there are multiple contributors to feeding problems supports a threshold hypothesis for retching and lends credibility to the maxim "retching is rarely reflux." Heuristics that respect surgical constraints on gastric performance, physiological scaling, and the whole patient yield improved growth and tolerance even in complex patients.